Flood risk assessment in the Lisbon Metropolitan Area - Santos, Pedro Pinto (2023)
Flood processes are one of the most challenging to risk assessment and management. In many situations, peak flows are generated kilometers away from the places where inundation is observed. Scale in flood risk assessments is a fundamental factor when estimating hazard, exposure, and vulnerability. Municipal, civil parish, and building-level information are used to construct flood risk indexes and profiles. It is observed that, depending on the scale at which it is represented, the same root information provides distinct insights into flood risk expression in the Lisbon Metropolitan Area. When compared with the Flood Directive critical areas, the results show they are mostly consistent with the results at the different scales, identifying the same hotspots of flood risk (in the Loures, V. F. Xira, and Setúbal municipalities) as those selected during the Directive’s implementation. Flood loss reduction implies the involvement of distinct risk practitioners and decision-makers, acting at distinct scales and sectors related to risk governance. Interconnections between flood risk components and between flood processes and other potential cascading processes are still insufficiently known and require the priority of society.